Originally Posted by
Peritus $\displaystyle Z_{out1} = \left( {R + \frac{1}
{{jwc}}} \right)||\frac{1}
{{jwc}} = \frac{{1 + Rjwc}}
{{2jwc - Rw^2 c^2 }}$
now we use voltage divider:
$\displaystyle
V_{out1} = V_{in} \frac{{Z_{out1} }}
{{Z_{out1} + R}}
$
now we'll use the voltage divider again:
$\displaystyle
V_{out} = V_{out1} \frac{{\frac{1}
{{jwc}}}}
{{R + \frac{1}
{{jwc}}}} = V_{out1} \frac{1}
{{1 + Rjwc}} =
$
$\displaystyle
= V_{in} \frac{{Z_{out1} }}
{{Z_{out1} + R}}\frac{1}
{{1 + Rjwc}}
$
$\displaystyle
H_{out} (jw) = \frac{{Z_{out1} }}
{{Z_{out1} + R}}\frac{1}
{{1 + Rjwc}}
$